Uncovering the Gender Participation Gap in the Crime Market - Evelina Gavrilova; Nadia Campaniello (Institute for the Study of Labor (IZA), 2015)
Using data from the U.S. National Incident Based Reporting System we document a gender gap in the number of crimes committed in the property crime market: only 30% of the crimes are committed by women. Starting from the classical Becker's model on crime we investigate some potential reasons for the participation gap looking at the differential incentives, measured in terms of earnings and probability of arrest. We observe that women obtain on average 32% less criminal earnings and face a 10% higher probability of arrest with respect to males. Once we account for type of crime and the attributes of offending, such as weapons, we find that the earnings gap is zero on average, while females still face a 1% higher probability of arrest than males. We also observe that females sort into offense types, characterized by a lower variation in the earnings risk, which reveals that females in the crime market are more risk averse than males. Furthermore, we analyze the participation gap by looking at the perceived incentives. We estimate the elasticities of crime with respect to the expected earnings and to the expected probability of not being arrested for both genders. We find that males respond to both these incentives, while females respond less to the incentive for higher earnings than males and they do not respond to the probability of arrest. Finally, we use a Blinder-Oaxaca type decomposition technique to measure crime differentials between females and males that arise due to different responses to incentives. We find that, in a counter factual scenario where the female elasticities increase to the level of the male ones, women would commit 40% more crimes than they actually do, reducing the male-female participation gap by almost 50%.
Keywords: J71; J16; K42; 330; participation gap; gender discrimination; crime